If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2 + 2x) = -4(-1x + -10) (2 * 7 + 2x * 7) = -4(-1x + -10) (14 + 14x) = -4(-1x + -10) Reorder the terms: 14 + 14x = -4(-10 + -1x) 14 + 14x = (-10 * -4 + -1x * -4) 14 + 14x = (40 + 4x) Solving 14 + 14x = 40 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 14 + 14x + -4x = 40 + 4x + -4x Combine like terms: 14x + -4x = 10x 14 + 10x = 40 + 4x + -4x Combine like terms: 4x + -4x = 0 14 + 10x = 40 + 0 14 + 10x = 40 Add '-14' to each side of the equation. 14 + -14 + 10x = 40 + -14 Combine like terms: 14 + -14 = 0 0 + 10x = 40 + -14 10x = 40 + -14 Combine like terms: 40 + -14 = 26 10x = 26 Divide each side by '10'. x = 2.6 Simplifying x = 2.6
| 2(x+1)+1.75=6.25 | | 16y+3y=44 | | 7x^2-101x+130=0 | | -8=1.5x+4 | | 2x+-10+79=180 | | 2q-17q+7-8= | | -7(2x+12)=162 | | -18=4n+2 | | 46=5x-4 | | -8/5=2/5(1)-2 | | [4t-8]=20 | | 5s^2t^3+30s^2t^2+45s^2t= | | x^3-16x^2+63x= | | 1*10y-4=2y+6 | | -4(7x+5)=-161 | | 12z+6(-15z+5)= | | -2?-2=4 | | -4(x+5)=-161 | | 9(11m-6)-8= | | 4x+9Y+27=0 | | -4(-5w+5)-3w=5(w-5)-5 | | [f+10]=1 | | 3-12-17y-8y= | | -4(-5w+5)-3w=5(w-5)-53 | | 3?6=18 | | 9(x+6)-5(2x-7)=22 | | -.5(z-2.4)=6 | | -11-18(8f+7)= | | 25=(.5)(6+4)(x) | | -4v=-23 | | -4(-5w+5)3w=5(w-5)-53 | | 8?-5=-40 |